PEMBERDAYAAN EKONOMI KERAKYATAAN MELALUI LEMBAGA KEUANGAN SYARÎ’AH - Wadhan - (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2009)
UKM is the business maker of the lowest level marketing. Theaim of the empowerment of UKM is that to grow and toaccelerate a strong business ability, independent, andcompetition power against abroad products. It is a proper choiceto use Syariah banking for UKM financing. Syariah banking has agreat opportunity to develop macro banking in order to reformIndonesian economy.